(untitled) (Bangladesh Veterinarian, 2017)
A virological survey for avian influenza (AI) and Newcastle disease (ND) was conducted in two selected live bird markets (LBMs), namely Kaptan Bazar and Karwan Bazar in Dhaka city, Bangladesh from August 2011 to July 2012. A total of 513 dead chickens were collected. An immune-chromatographic rapid antigen test for Type A influenza virus and both conventional and real time RT-PCR were used for the detection and characterization of AI and ND viruses. All carcasses were first screened by the rapid antigen test kit and 93 were positive for Type A influenza virus. RT-PCR on a representative number of rapid antigen test positive samples (n = 24) confirmed the presence of Type A influenza virus and mostly H5 influenza virus (22 out of 24 tested samples). Influenza rapid test negative samples (n = 420) were subjected to routine necropsy. Heat stress, suffocation and physical injury were the most common cause of mortality (163 cases), followed by ND, suspected to be the cause of 85 deaths. On molecular investigation of these 85 samples, the presence of ND virus was confirmed in 59 and AI virus in 6; 15 were negative for both ND and AI viruses and 5 were unsuitable for investigation. Among the 59 ND confirmed cases 18 also contained AI virus. In summary, out of 513 carcasses 117 (22.81%) contained AI virus and 59 (11.50%) contained ND virus. Eighteen (3.51%) carcasses contained both AI and ND viruses. The findings suggest that both AI and ND should be considered as major threats to the poultry industry. Bangl. vet. 2016. Vol. 33, No. 1, 8-15